(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
In this paper, the Multi-objective linear fractional programming problems with interval coefficients (MOLFPPIC) is considered. The aim of this paper is to show an iterative procedure that can be utilized to solve such problems. Questions of how to select the (best, worst) value for the objective functions, the nonlinear problem is changed into a linear programming problem (LPP), with two or more constraints and more than one varieties by two algorithms (1) subtracting the interval of numerator of the fractional from the interval of denominator and (2) the denominator to be one of the constraints. Finally, after we solve each objective function without intervals individually by modified simplex method, we use a new technique via transforming it to single-objective function with the same constraints. Numerical examples are illustrated to show the efficiency of these algorithms and new technique.